Dampak Kebijakan Sekolah Tentang Poin Pelanggaran Tata Tertib Siswa dalam Membentuk Perilaku Siswa yang Berkarakter - Muhammad Solihuddin (Jurnal Kebijakan dan Pengembangan Pendidikan, 2013)
This study aims to: 1). models describe the implementation of school policies on student discipline infraction points 2). describing the constraints in the implementation of school policies on student discipline infraction points, 3). describing the efforts to overcome obstacles in implementing school policies on student discipline infraction points. 4). describe the impact of school policies on student discipline violations points in SMP 4 Mejayan. Researchers observed an existing policy using observations, interviews and document research. The results showed: 1). student discipline violation points is to use a points system violation, 2). Constraints in the implementation of student discipline include non-physical barriers and physical barriers to the school environment, 3). Efforts to overcome barriers to the implementation of the order of students is done by principal's conduct coaching teachers, staff, and all the elements that exist in the school, 4). the impact of school policies is the number of offenses committed students dropped dramatically, the behavior of the students have started to show the existence of such character behavior, discipline, respect for legal norms in force, responsible, healthy lifestyle